THE IMPLEMENTATION OF TOTAL QUALITY MANAGEMENT IN EDUCATION TO IMPROVE STAKEHOLDER SATISFACTION AND INSTITUTIONAL QUALITY - Jamaluddin; Evi Juliyanti; Elvirawati (SUKMA: Jurnal Pendidikan, 2026)
The increasing demand for accountability, competitiveness, and service quality in education has transformed how educational quality is conceptualized and evaluated. Educational institutions are no longer assessed solely based on academic outcomes but are also expected to meet the diverse expectations of stakeholders, including students, parents, and society. However, despite extensive discussions on educational quality and Total Quality Management (TQM), existing studies often address these aspects separately, resulting in a fragmented understanding of how quality management operates within educational systems. This study adopts a qualitative approach through a literature-based analysis of recent scholarly works to examine the integration of TQM and educational quality. The findings reveal that educational quality is a multidimensional system consisting of input, process, output, and outcome, interconnected through continuous improvement mechanisms. Furthermore, TQM provides a comprehensive framework that integrates stakeholder satisfaction as both an outcome and a feedback mechanism. This study contributes by proposing an integrative model that links TQM practices with stakeholder-oriented educational quality, offering a more holistic and adaptive approach to quality management in education.